Peran Pendidikan Agama Islam dalam Membangun Karakter Generasi Muslim di Era Modern - Ahmad Nasrudin; Ika Elsa Junita; Rini Suhestiwi; Dalima Septiria; Bambang Irawan (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2026)
Background: Technological developments in the modern era significantly impact education by providing easier access to information while posing new challenges for character development in the younger generation. This study analyzes the role of Islamic Religious Education in shaping Muslim generation character amidst modernization and identifies challenges arising from digital technology. Current moral crises manifest through problematic behaviors indicating weak internalization of religious values and insufficient synergy between educational institutions, families, and communities.Method: This study employs a library research methodology by reviewing relevant academic literature including journals, books, and scientific reports. This approach facilitates deep understanding of the research topic, theoretical analysis, and logical conclusion drawing regarding PAI function in character formation.Results: The findings demonstrate that PAI plays a central role in shaping Islamic character through internalizing values of honesty, discipline, responsibility, and tolerance. PAI serves as a moral bulwark protecting youth from negative technology impacts including decreased empathy and spiritual degradation. Obstacles include weak application of moral values in learning and lack of synergy between schools, families, and communities. While digital technology offers opportunities through virtual platforms, uncontrolled usage risks moral crises, necessitating wise integration that maintains alignment with Islamic values.Conclusion: PAI possesses an essential role in forming Muslim personalities with deep spiritual understanding while protecting students from modern era negative impacts through comprehensive Islamic teachings. Despite challenges regarding minimal ethical approaches and environmental influences, PAI must adapt to contemporary developments while maintaining Islamic identity and producing faithful generations with noble character.